Grass fires and road structure influence plant invasions in a critical wildlife habitat in north-eastern India. (3rd June 2023) - Banerjee, Subham; Das, Amit; Rahman, Masidur; Bhowal, Swapnil; Das, Dhritiman; John, Robert
Summary: One of the multiple threats to protected areas worldwide, invasive plant species have the potential to decrease biodiversity and ecosystem function. We studied changes in infestation by two widespread invasive plant species – Chromolaena odorata and Mikania micrantha – in India's Manas National Park, a critical conservation site for threatened flora and fauna. Based on field surveys in 2011 and 2019, we found that C . odorata and M . micrantha were present in most of the sampled plots and had newly invaded over 20% of the plots. However, the abundance of M. micrantha decreased in 45% of the plots while C. odorata increased in >50% of the plots. We used a decision tree-based regression with environmental variables as predictors to generate the distribution, abundance and invasion risk maps of the two species. Among environmental variables, road proximity and fire frequency had the strongest influences, respectively, on C. odorata and M. micrantha . Invaded quadrats exhibited lower native-plant diversity than non-invaded quadrats, and C. odorata specifically had a strong negative association with native-plant community structure. These invasive species have increased their range and abundance, and our predicted invasion risk maps indicate the areas where management intervention is urgently needed.